Marine spatial plans focusing on biodiversity conservation: The case of the Aegean Sea. Issue 8 (25th May 2021) - Markantonatou, Vasiliki; Giakoumi, Sylvaine; Koukourouvli, Nikoletta; Maina, Irida; Gonzalez‐Mirelis, Genoveva; Sini, Maria; Maistrelis, Kostas; Stithou, Mavra; Gadolou, Eleni; Petza, Dimitra; Kavadas, Stefanos; Vassilopoulou, Vasiliki; et al.
Abstract: The expansion and intensification of marine uses have severe cumulative impacts on marine ecosystems and human well‐being, unless they are properly managed with an ecosystem‐based management approach. A systematic conservation planning approach, using marxan with zones, was applied to generate alternative marine spatial plans for the Aegean Sea. Relevant human uses were included and their cumulative impact on a wide set of key biodiversity features was considered in the analysis. Different cost scenarios were developed to gain insight on the effects of the approaches used to assess socio‐economic factors, and their potential impact on spatial plans. The spatial plans generated differed greatly depending on the method used to estimate opportunity costs and evaluate human activities in monetary terms. The vulnerability weights (the relative vulnerability of ecological features to specific human activities and their impacts) that were estimated based on a cumulative impact assessment, allowed the assessment of each zone in contributing to the achievement of conservation targets, through a transparent planning approach. Results indicate that special care should be given to how socio‐economic activities, their impact on the ecosystems, and related costs are incorporated into planning. The proposed approach demonstrates how EU member states may effectively comply with the new Biodiversity Strategy 2030 targets, while planning for the sustainable use of their marine resources.